2005
DOI: 10.1128/aem.71.6.3131-3136.2005
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Real-Time PCR Assays for Detection of Human Adenoviruses and Identification of Serotypes 40 and 41

Abstract: A quantitative real-time TaqMan PCR assay for detection of human adenoviruses (HAdV) was developed using broadly reactive consensus primers and a TaqMan probe targeting a conserved region of the hexon gene. The TaqMan assay correctly identified 56 representative adenovirus prototype strains and field isolates from all six adenovirus species (A to F). Based on infectious units, the TaqMan assay was able to detect as few as 0.4 and 0.004 infectious units of adenovirus serotype 2 (AdV2) and AdV41, respectively, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
153
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(160 citation statements)
references
References 29 publications
1
153
1
5
Order By: Relevance
“…The sequences and sources of the primers and probes used in this present study are shown in Table 1 . [28][29][30][31][32] Each assay was validated using positive controls and negative controls consisting of non-target NA and DEPCtreated water.…”
Section: Methodsmentioning
confidence: 99%
“…The sequences and sources of the primers and probes used in this present study are shown in Table 1 . [28][29][30][31][32] Each assay was validated using positive controls and negative controls consisting of non-target NA and DEPCtreated water.…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous studies, the standard cur ve was generated as follows [7][8][9] : Standard DNA from S. enteritidis was used to establish a standard curve. The standard DNA contained amplified target DNA in different quantities which was included in each LightCycler run.…”
Section: Fq-pcr Standard Curvementioning
confidence: 99%
“…Given the localization of 55R E1A in the nucleus during infection, we sought to assess whether, akin to the largest E1A isoforms, 55R E1A could activate viral gene expression. To accomplish this, we performed a qRT-PCR assay on contact-inhibited human diploid IMR-90 fibroblast cells infected with dl309, JM17-55R, dl521, or dl312, using primers that recognize transcripts expressed from selected viral promoters (1,13,18). The E1A products expressed by each of these viruses are listed in Fig.…”
Section: Resultsmentioning
confidence: 99%